High-lead fly ash compounded industrial solid waste fired ceramsite and preparation method thereof
Patent Information
- Application Number
- CN202611069081.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-17
- Publication Date
- 2026-10-20
AI Technical Summary
[0012]本发明的目的在于提供一种高铅飞灰复配工业固废烧制的陶粒及其制备方法以解决现有技术存在多固废仅简单混合、复配方案针对性不足、重金属稳定固化能力不足、无法实现高重金属(高铅)飞灰资源化浸出达标等问题
(1)本发明实现了飞灰中重金属的高效固化,无需外加化学稳定剂,降低处理成本。飞灰中Pb、Zn、Cu、Cr等重金属在高温下,主要通过磷酸盐和铁酸盐等形式形成难溶性矿物,牢固的固化在晶格中。剩余重金属一部分与高钙粉煤灰释放的 CaO反应生成难溶性碳酸盐、氢氧化物,另一部分被烧成过程中形成的玻璃体紧密包裹,同时细飞灰的玻璃相前驱体促进矿物相固化,最终所有重金属浸出浓度均满足国标限值要求,其中Pb浸出浓度<0.5mg/L;且水洗预处理去除了飞灰中大部分可溶性氯盐,避免氯盐高温挥发造成设备腐蚀及二次污染,烧成工艺将残余氯离子部分固化在玻璃体和氧化物晶格中,降低氯盐对重金属固化的干扰。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention belongs to the field of solid waste resource utilization technology, specifically relating to a type of ceramsite made from high-lead fly ash compounded with industrial solid waste and its preparation method, and more specifically, a type of ceramsite made from high-lead-content municipal solid waste incineration fly ash, compounded with municipal sludge, high-calcium fly ash, bentonite and other industrial solid waste and its preparation method. Background Technology
[0002] Fly ash from municipal solid waste incineration is a hazardous solid waste generated during waste-to-energy incineration. It is listed as Category HW18 in the National Hazardous Waste List and is rich in highly leaching toxic heavy metals such as zinc, lead, copper, cadmium, and chromium, with excessive lead content being a particularly prominent issue. Furthermore, fly ash contains large amounts of soluble chlorides and trace amounts of dioxins; improper disposal can easily lead to serious secondary pollution.
[0003] Currently, the mainstream disposal methods for fly ash from municipal solid waste incineration are chelation stabilization followed by secure landfill or pre-treatment with water washing followed by co-processing in cement kilns. However, landfilling has drawbacks such as high disposal costs, large land occupation, and serious resource waste. While water washing can remove more than 80% of chlorides from fly ash, it cannot completely remove residual heavy metals. Furthermore, co-processing in cement kilns imposes extremely stringent limits on the chloride content of the washed ash, resulting in high requirements and high processing costs. In contrast, using washed fly ash as raw material to prepare building materials such as expanded clay aggregates has relatively lower requirements for controlling pollutants such as chlorides, heavy metals, and dioxins. Moreover, the expanded clay aggregates require high-temperature calcination at temperatures above 1100℃, which can effectively decompose dioxins and solidify some chlorides and heavy metals. Therefore, this technology has promising application prospects.
[0004] Despite this, while ceramsite exhibits some solidification ability for heavy metals during high-temperature sintering, there are still risks of decreased solidification efficiency and potential leaching for high-content heavy metals. The content of heavy metals (represented by lead, zinc, and cadmium) in fly ash in my country shows significant regional differences, generally exhibiting a distribution pattern of higher levels in the south and lower levels in the north. In most parts of southern China and parts of the Beijing-Tianjin-Hebei region, the lead and zinc content in fly ash reaches over 2000 mg / kg. Conventional oxidation crystallization and vitreous lattice solidification alone are far from sufficient to meet leaching toxicity standards. Therefore, it is urgent to optimize raw material ratios and enhance the lattice coating and chemical bonding of heavy metals to improve lead solidification, ensuring long-term leaching stability while meeting heavy metal leaching standards.
[0005] Studies have shown that Pb under high temperature conditions 2+ Can be used with PO4 3- The reaction produces highly stable lead phosphate (Pb3(PO4)2) and lead pyrophosphate (Pb2P2O7), which are found in Cl... -With the participation of these substances, extremely insoluble lead phosphate (Pb5(PO4)3Cl) can be formed. Simultaneously, during the molding process of aluminosilicate ceramics, increasing the iron and calcium ratio within the system can significantly promote the retention of lead ions in the aluminosilicate glass, further reducing the risk of lead leaching. Among these, phosphogypsum and phosphate slag are rich in phosphate and calcium ions, making them excellent lead solidifying agents; red mud, steel slag, and other iron-rich solid wastes contain Fe... 2+ / Fe 3+ It can react with lead to form stable lead ferrite minerals (PbFe2O4), enhancing the solidification effect of lead, and PO4 3- with Fe 2+ / Fe 3+ It also exhibits excellent solidification effects on various heavy metals such as zinc, cadmium, and copper. Developing a synergistic combination of the aforementioned industrial solid waste and washed fly ash can create a suitable high-temperature melting and foaming environment, ensuring the full and thorough mineral reactions related to heavy metal solidification.
[0006] Although existing technologies for the resource utilization of fly ash from waste incineration to prepare ceramsite have made some progress, they generally suffer from problems such as poor adaptability to the treatment of high-lead fly ash, difficulty in controlling heavy metal leaching, cumbersome processes and high energy consumption, extensive raw material pretreatment, and difficulty in achieving low-cost, large-scale, high-value utilization. These issues make it difficult to meet the actual needs for large-scale, harmless, stable, and co-processing of high-lead fly ash. For example:
[0007] Patent CN10135784A uses a non-fired chemical stabilization-coating curing process to prepare fly ash ceramsite. Although it can fix some heavy metals by chemical chelation and surface coating without high-temperature sintering, it is only a short-term physical preservation and chemical chelation. It does not form a high-temperature mineral stable solidification structure, resulting in poor treatment effect on high-lead fly ash and inability to decompose dioxins, posing a long-term risk of leaching pollution. At the same time, this process does not perform water washing, grading and dechlorination treatment on fly ash. The residue of easily soluble salts will reduce the durability of ceramsite. It lacks multi-solid waste functional compatibility design, and the physical and chemical properties of the product fluctuate greatly. It can only be used as ordinary low-end aggregate and is difficult to achieve high-value utilization.
[0008] Patent CN113387715A uses hydrothermal pretreatment followed by low-temperature sintering at 900-1000℃ to prepare fly ash ceramsite. Although this can reduce the sintering temperature and improve the basic strength, the process is cumbersome, requiring multiple water washings, long-term hydrothermal treatment, and segmented drying. This results in high water and energy consumption and generates a large amount of saline wastewater. Furthermore, it does not set targeted solidification components for high-lead fly ash, making it difficult to achieve the required heavy metal leaching. At the same time, it does not perform particle size classification and structured granulation design, resulting in unreasonable raw material compatibility. Sintering is prone to component segregation, leading to loose and cracked ceramsite, and posing a risk of pollutant volatilization and long-term leaching.
[0009] The patent CN116444292A describes a process for high-temperature sintering of fly ash ceramsite with waste fiberglass, coal gangue, and sludge. While this process can improve cylinder compressive strength and achieve solid waste utilization, the sintering temperature is as high as 1050–1250℃, the holding time is long, and energy consumption is relatively high. The raw materials require a long aging period of 3–12 days, resulting in a large footprint, low production efficiency, and the lack of pre-washing of fly ash for dechlorination and lead removal. At high temperatures, this process is prone to chloride corrosion of equipment and precipitation of heavy metals. The process lacks a synergistic lead mineralization design with phosphorus, iron, and calcium, relying solely on simple melting and coating, which has poor long-term solidification effect on high-lead fly ash. Furthermore, the lack of particle size classification and "core-shell" granulation design results in poor product uniformity.
[0010] Patent CN120864865A uses shale combined with sludge and fly ash to sinter ceramsite in a three-stage rotary kiln. Although it can achieve solid waste disposal and lightweight building material preparation, it does not perform water washing and classification pretreatment on the fly ash. Soluble chlorine and residual lead cannot be removed in advance. There is no targeted lead-fixing mineral formula system. It only relies on simple encapsulation with ordinary glass, which makes it difficult to achieve stable mineralization and fixation of heavy metals. There is a long-term risk of secondary pollution from leaching. In addition, it does not use the "core-shell" granulation process, which makes the raw material prone to cracking and the yield of finished products is low.
[0011] In conclusion, developing a multi-solid waste co-firing technology for high-lead fly ash that combines efficient heavy metal solidification and stabilization with good physicochemical properties of ceramsite has significant environmental and economic benefits. Summary of the Invention
[0012] The purpose of this invention is to provide a ceramic aggregate made from high-lead fly ash compounded with industrial solid waste and its preparation method to solve the problems of existing technologies, such as simple mixing of multiple solid wastes, insufficient targeting of compounding schemes, insufficient ability to stabilize and solidify heavy metals, and inability to achieve the leaching of high-heavy-metal (high-lead) fly ash resources to meet standards.
[0013] To achieve the above objectives, the present invention employs the following: A type of ceramsite made from high-lead fly ash and compound industrial solid waste is composed of the following raw materials by mass percentage: 10%–15% of fine fly ash after water washing, 15%–20% of coarse fly ash after water washing, 20%–35% of municipal sludge, 15%–25% of high-calcium fly ash / coal gangue, 3%–5% of bentonite or clay, 3%–5% of phosphogypsum or phosphorus slag, and 2%–4% of red mud or steel slag.
[0014] Preferably, the raw materials are expressed as a percentage by mass as follows: The composition of the fly ash is as follows: fine fly ash after water washing 12%~14%, coarse fly ash after water washing 16%~18%, municipal sludge 25%~30%, high-calcium fly ash / coal gangue 18%~22%, bentonite or clay 3%~4%, phosphogypsum or phosphorus slag 4%~5%, and red mud or steel slag 2%~3%.
[0015] Preferably, the washed fine fly ash is obtained by deep washing (liquid-to-solid ratio > 8 mL / g) of municipal solid waste incineration fly ash to remove chloride, followed by drying at 105°C to constant weight. It is rich in metal oxides and glassy phase precursors. The washed fine fly ash contains chloride ion content < 2%, lead content < 100 mg / Kg, soluble lead content < 15 mg / Kg, and particle size ≤ 20 μm. The washed coarse fly ash is obtained by washing and dechlorinating municipal solid waste incineration fly ash, then crushing and shaping the coarse particles obtained from the decomposition, and drying them at 105℃ to constant weight. Its particle structure is dense and its mineral phase is stable. The washed coarse fly ash contains chloride ion content <2.5%, lead content <150 mg / Kg, soluble lead content <20 mg / Kg, and particle size of 20~120 μm.
[0016] Preferably, the municipal sludge has a moisture content of ≤15% and a particle size of ≤0.15 mm; The high-calcium fly ash or coal gangue has a CaO content ≥15% and a particle size ≤0.075 mm. The bentonite or clay has an expansion capacity ≥15 mL / g and a particle size ≤0.075 mm; The phosphogypsum or phosphate slag has a P2O5 content of ≥8% and a particle size of ≤0.075 mm. The red mud or steel slag has an Fe2O3 content of ≥15% and a particle size of ≤0.075 mm.
[0017] Preferably, the bulk density of the ceramsite is 450~750 kg / m³. 3 The cylinder compressive strength is ≥0.8 MPa, the water absorption rate is 10~16%, and the yield is ≥90%; the leaching concentration of heavy metal Pb is <0.5 mg / L, and the leaching concentration of all heavy metals meets the limit requirements of the "Identification Standard for Hazardous Waste - Leaching Toxicity Identification" (GB 5085.3-2007).
[0018] This invention further protects the method for preparing ceramsite from the above-mentioned high-lead fly ash compound industrial solid waste, comprising the following steps: S1. Weigh out the following ingredients according to the proportions: fine fly ash after water washing, municipal sludge, high-calcium fly ash or coal gangue, bentonite or clay, phosphogypsum or phosphorus slag, red mud or steel slag, and mix them evenly to obtain matrix powder. S2. The washed coarse fly ash is added to the matrix powder as aggregate, and the "core-shell" granulation process is adopted. The washed coarse fly ash particles are used as the core, and the matrix powder is evenly coated on its surface. Water is added to moisten and form spherical raw material. S3. The raw material pellets are dried, preheated, sintered, and cooled to obtain lightweight ceramsite.
[0019] Preferably, the mixing in step S1 is performed using a twin-shaft mixer for 10–15 min; The spherical raw material described in step S2 has a moisture content of 12% to 15% and a particle size of 6 to 12 mm.
[0020] Preferably, in step S3, the drying temperature is 100–300 °C, and the holding time is 20–30 min; the preheating temperature is 300–600 °C, and the holding time is 15–20 min; the sintering temperature is 1120–1180 °C, and the holding time is 20–30 min under an oxidizing atmosphere; and the cooling is achieved by air cooling.
[0021] Preferably, the excess air coefficient of the oxidizing atmosphere is >1.5.
[0022] This invention further protects the application of the above-mentioned ceramsite in the preparation of landscaping substrates, lightweight fillers, or water treatment ecological filter media.
[0023] Compared with the prior art, the present invention provides a method for preparing ceramsite from high-lead fly ash compounded with industrial solid waste, which has the following beneficial effects: (1) This invention achieves efficient solidification of heavy metals in fly ash without the need for external chemical stabilizers, thus reducing processing costs. At high temperatures, heavy metals such as Pb, Zn, Cu, and Cr in fly ash mainly form insoluble minerals through phosphates and ferrates, which are firmly solidified in the crystal lattice. Some of the remaining heavy metals react with CaO released from high-calcium fly ash to form insoluble carbonates and hydroxides, while the other part is tightly encapsulated by the glass phase formed during the calcination process. At the same time, the glass phase precursor of fine fly ash promotes the solidification of the mineral phase. Ultimately, the leaching concentration of all heavy metals meets the national standard limit requirements, with the Pb leaching concentration <0.5 mg / L. Furthermore, the water washing pretreatment removes most of the soluble chloride salts in the fly ash, avoiding high-temperature volatilization of chloride salts that could cause equipment corrosion and secondary pollution. The calcination process partially solidifies the residual chloride ions in the glass phase and oxide lattice, reducing the interference of chloride salts on the solidification of heavy metals.
[0024] (2) This invention realizes the synergistic utilization of multi-source solid waste, without chemical additives, realizes the substitution of natural raw materials, significantly reduces the cost of ceramsite raw materials, and solves the disposal problems of various typical solid wastes such as water-washed fly ash, municipal sludge, high-calcium fly ash / coal gangue, bentonite / clay, phosphogypsum / phosphorus slag, red mud / steel slag, etc., realizing "using waste to treat waste and turning waste into treasure", with significant environmental and economic benefits.
[0025] (3) The present invention adopts a graded particle size design of “coarse fly ash skeleton + fine powder matrix” and a “core-shell” granulation process, which not only ensures the mechanical strength of raw material balls and prevents cracking during the drying and preheating stages, but also facilitates expansion and foaming and uniform distribution of pores during the firing process. The yield of ceramsite is ≥90%. The preparation process is compatible with the existing ceramsite production line, does not require large-scale equipment modification, and does not require deep chemical stabilization treatment of fly ash. The process steps are simple, the energy consumption is low, and it is suitable for industrial-scale promotion.
[0026] (4) The ceramsite prepared by this invention has stable physical properties, meets the requirements for non-structural applications, and has a bulk density of 450-750 kg / m³. 3 The compressive strength is ≥0.8 MPa, and the water absorption rate is 10-16%. The particles are round and dense, and the internal structure is uniform and porous. It has good air permeability and water retention. It can be widely used in landscaping substrate, lightweight filler, water treatment ecological filter material and other fields. It has a wide range of applications. Attached Figure Description
[0027] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the accompanying drawings involved in the embodiments are now briefly described. Obviously, the drawings in the following description are merely illustrative of some embodiments of the present invention. For those skilled in the art, other forms of drawings can be constructed based on these drawings without creative effort.
[0028] Figure 1 This is an overall process flow diagram of the method for preparing ceramsite from high-lead fly ash compounded with industrial solid waste proposed in this invention. Figure 2 This is a photograph of the ceramsite after firing according to the present invention; Figure 3 This is a microscopic SEM image of the ceramsite after firing, as presented in this invention. Detailed Implementation
[0029] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0030] Please see Figure 1This invention proposes a method for preparing ceramsite from high-lead fly ash compounded with industrial solid waste. It involves precisely compounding coarse and fine fly ash (washed and graded) with municipal sludge, high-calcium fly ash / gangue, phosphogypsum / phosphorus slag, and red mud / steel slag. By controlling the composition of the silica-alumina-calcium-iron-phosphorus mineral system, while ensuring the ceramsite's skeletal support and foaming pores, high-temperature mineralization, lattice coating, and chemical bonding are used to enhance lead and heavy metal solidification. The invention also discloses an optimal firing temperature for heavy metal solidification. High-temperature sintering at 1120-1180℃ in an oxidizing atmosphere promotes directional mineral reactions between heavy metals such as lead, zinc, copper, and chromium and phosphate and iron-aluminum components, generating thermodynamically stable phases such as lead phosphate, lead chloride phosphate, and ferrates. This constructs a dual solidification mechanism of mineral lattice chemical solidification and silica-alumina glass physical encapsulation, solving the problems of easy heavy metal leaching, difficulty in achieving high-lead fly ash standards, and high long-term leaching risk caused by simple melt-coating processes.
[0031] The following description, in conjunction with the accompanying drawings and specific examples, further illustrates the ceramsite produced by calcining high-lead fly ash and industrial solid waste, and its preparation method. The specific details are as follows.
[0032] Example 1: This embodiment proposes a method for preparing ceramsite by compounding industrial solid waste with water-washed fly ash, as detailed below: 1. Ingredients (percentage by weight): The composition of the fly ash is as follows: 12% fine fly ash after washing, 16% coarse fly ash after washing, 25% municipal sludge, 18% high-calcium fly ash, 3% bentonite, 4% phosphogypsum, and 2% red mud.
[0033] 2. Raw material particle size requirements: After washing, fine fly ash is ≤20 μm, coarse fly ash is 20~120 μm, municipal sludge is ≤0.15 mm, high-calcium fly ash is ≤0.075 mm, bentonite is ≤0.075 mm, phosphogypsum is ≤0.075 mm, and red mud is ≤0.075 mm.
[0034] 3. Preparation method: Step 1: Weigh out the washed fine fly ash, municipal sludge, high-calcium fly ash, bentonite, phosphogypsum, and red mud from the above raw materials according to the proportion, put them into a twin-shaft mixer and stir for 10 minutes until they are evenly mixed to obtain the matrix powder. Step 2: Add the washed coarse fly ash and use the "core-shell" granulation process. The washed coarse fly ash particles are used as the core. The mixture is sprayed with water to make the moisture content of the mixture 12%. The matrix powder is evenly coated on the surface of the coarse fly ash particles to make spherical raw materials with a particle size of 6-8 mm. Step 3: After screening, the raw material balls are fed into a rotary kiln and processed sequentially through a drying section, a preheating section, a firing section, and a cooling section. The drying section is held at 100 ℃ for 30 min; the preheating section is held at 300 ℃ for 20 min; the firing section is held at 1120 ℃ in an oxidizing atmosphere for 20 min; after firing, the balls are rapidly cooled by air and then naturally cooled to room temperature to obtain ceramsite.
[0035] 4. Product performance: The bulk density of the ceramsite prepared in this embodiment is 450 kg / m³. 3 The compressive strength of the cylinder is 0.8 MPa, the water absorption rate is 16%, and the yield is 90%. According to the "Identification Standard for Hazardous Waste - Leaching Toxicity Identification" (GB 5085.3-2007), the leaching concentrations of Pb, Zn, Cu, and Cr are 0.20 mg / L and 0.23 mg / L, respectively, all meeting the standard limits. The particles are round, with uniform internal pores and a dense surface.
[0036] Example 2: This embodiment proposes a formulation and preparation method for producing ceramsite from industrial solid waste using water-washed fly ash and compounded materials, as detailed below: 1. Ingredients (percentage by weight): The composition of the fly ash is as follows: 13% fine fly ash after washing, 17% coarse fly ash after washing, 28% municipal sludge, 20% coal gangue, 3.5% clay, 4.5% phosphorus slag, and 3% steel slag.
[0037] 2. Raw material particle size requirements: After washing, the fine fly ash is ≤20 μm, the coarse fly ash is 20~120 μm, the municipal sludge is ≤0.15 mm, the coal gangue is ≤0.075 mm, the clay is ≤0.075 mm, the phosphorus slag is ≤0.075 mm, and the steel slag is ≤0.075 mm.
[0038] 3. Preparation method: Step 1: Weigh out the washed fly ash, municipal sludge, coal gangue, clay, phosphorus slag and steel slag from the above raw materials according to the proportion, put them into a twin-shaft mixer and stir for 12 minutes until they are evenly mixed to obtain matrix powder. Step 2: Add the washed coarse fly ash and use the "core-shell" granulation process. The washed coarse fly ash particles are used as the core. The mixture is sprayed with water to make the moisture content of the mixture 13.5%. The matrix powder is evenly coated on the surface of the coarse fly ash particles to make spherical raw materials with a particle size of 8-10 mm. Step 3: After screening, the raw material pellets are fed into a rotary kiln and processed sequentially through a drying section, a preheating section, a firing section, and a cooling section. The drying section temperature is 200 ℃ and held for 25 min; the preheating section temperature is 450 ℃ and held for 18 min; the firing section temperature is 1150 ℃ and held for 25 min under an oxidizing atmosphere; after firing, the pellets are rapidly cooled by air and then naturally cooled to room temperature.
[0039] 4. Product performance: The bulk density of the ceramsite prepared in this embodiment is 600 kg / m³. 3 The compressive strength of the cylinder is 1.2 MPa, the water absorption rate is 13%, and the yield is 95%. According to the "Identification Standard for Hazardous Waste - Leaching Toxicity Identification" (GB 5085.3-2007), the leaching concentrations of Pb, Zn, Cu, and Cr are 0.17 mg / L and 0.19 mg / L, respectively, all of which meet the standard limits. The particles have high sphericity, uniform internal porous structure, and good air permeability and water retention.
[0040] Example 3: This embodiment proposes a formulation and preparation method for producing ceramsite from industrial solid waste using water-washed fly ash and compounded materials, as detailed below: 1. Ingredients (percentage by weight): The mixture consists of 15% fine fly ash after washing, 20% coarse fly ash after washing, 35% municipal sludge, 15% high-calcium fly ash, 5% bentonite, 5% phosphogypsum, and 4% red mud.
[0041] 2. Raw material particle size requirements: After washing, fine fly ash is ≤20 μm, coarse fly ash is 20~120 μm, municipal sludge is ≤0.15 mm, high-calcium fly ash is ≤0.075 mm, bentonite is ≤0.075 mm, phosphogypsum is ≤0.075 mm, and red mud is ≤0.075 mm. 3. Preparation method: Step 1: Weigh out the washed fine fly ash, municipal sludge, high-calcium fly ash, bentonite, phosphogypsum, and red mud from the above raw materials according to the proportions, and put them into a twin-shaft mixer and mix for 15 minutes to form a uniform matrix powder. Step 2: Add the washed coarse fly ash and use the "core-shell" granulation process. The washed coarse fly ash particles are used as the core. Spray water to wet the mixture and control the moisture content of the mixture to 15%. The matrix powder is evenly coated on the surface of the coarse fly ash particles to make spherical raw materials with a particle size of 10-12 mm. Step 3: After screening, the raw material balls are fed into a rotary kiln and processed sequentially through a drying section, a preheating section, a firing section, and a cooling section. The drying section is held at 300℃ for 20 minutes; the preheating section is held at 600℃ for 15 minutes; and the firing section is held at 1180℃ in an oxidizing atmosphere for 30 minutes. After firing, the balls are rapidly cooled by air and then naturally cooled to room temperature to obtain ceramsite.
[0042] 4. Product performance: The ceramsite prepared in this embodiment has a bulk density of 750 kg / m³, a compressive strength of 1.5 MPa, a water absorption rate of 10%, and a yield of 92%. According to the "Identification Standard for Hazardous Waste: Leaching Toxicity Identification" (GB 5085.3-2007), the leaching concentrations of Pb, Zn, Cu, and Cr were 0.42 mg / L, 0.80 mg / L, 0.22 mg / L, and 0.25 mg / L, all meeting the standard limits. The particles are dense, exhibit excellent mechanical properties, and can be directly used as lightweight fillers.
[0043] The ceramsite prepared in Examples 1-3 was observed and tested, and the following results were obtained: like Figure 2 As shown, after firing, the ceramsite is round and spherical, with regular particle shape, uniform particle size, dense and solid surface structure, and local natural micropores. The overall quality is good, which is consistent with the typical appearance characteristics of lightweight ceramsite produced from resource-based solid waste.
[0044] like Figure 3 As shown in the microscopic morphology, it can be clearly seen that the ceramsite matrix particles are tightly bonded, and the overall structure is dense. Natural micropores exist on the surface and inside, the particles are regularly packed and arranged, the interfacial bonding is good, and the overall structure is uniform and stable.
[0045] Table 1-2 can be obtained by combining the contents of Examples 1-3: Table 1. Chemical composition of ceramsite in the three examples (mass fraction, %)
[0046] As shown in Table 1, the ceramsite prepared in Examples 1 to 3 is mainly composed of SiO2, Al2O3, CaO and Fe2O3, and also contains an appropriate amount of P2O5, which is beneficial for the phosphate mineralization and fixation of heavy metals such as lead.
[0047] Table 2 Element leaching concentrations in the three embodiments
[0048] As shown in Table 2, the leaching concentrations of Pb, Zn, Cu, and Cr in the ceramsite prepared in Examples 1-3 are all far below the limits specified in the "Identification Standard for Hazardous Waste: Leaching Toxicity Identification" (GB 5085.3-2007). Among them, the leaching concentration of Pb is below 0.5 mg / L, indicating that the present invention achieves efficient stabilization and solidification of heavy metals through the synergistic mineralization of phosphorus, iron, and calcium and the dual solidification mechanism of the "core-shell" structure.
[0049] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A type of ceramsite produced from high-lead fly ash compounded with industrial solid waste, characterized in that, By weight percentage, it consists of the following raw materials: 10%–15% of fine fly ash after water washing, 15%–20% of coarse fly ash after water washing, 20%–35% of municipal sludge, 15%–25% of high-calcium fly ash / coal gangue, 3%–5% of bentonite or clay, 3%–5% of phosphogypsum or phosphorus slag, and 2%–4% of red mud or steel slag.
2. The ceramsite according to claim 1, characterized in that, The raw materials are expressed as a percentage by mass as follows: The composition of the fly ash is as follows: fine fly ash after water washing 12%~14%, coarse fly ash after water washing 16%~18%, municipal sludge 25%~30%, high-calcium fly ash / coal gangue 18%~22%, bentonite or clay 3%~4%, phosphogypsum or phosphorus slag 4%~5%, and red mud or steel slag 2%~3%.
3. The ceramsite according to claim 1, characterized in that, The washed fine fly ash has a chloride ion content of <2%, a lead content of <100 mg / Kg, a soluble lead content of <15 mg / Kg, and a particle size of ≤20 μm. The washed coarse fly ash has a chloride ion content of <2.5%, a lead content of <150 mg / Kg, a soluble lead content of <20 mg / Kg, and a particle size of 20~120 μm.
4. The ceramsite according to claim 1, characterized in that, The municipal sludge has a moisture content of ≤15% and a particle size of ≤0.15 mm. The high-calcium fly ash or coal gangue has a CaO content ≥15% and a particle size ≤0.075 mm. The bentonite or clay has an expansion capacity ≥15 mL / g and a particle size ≤0.075 mm; The phosphogypsum or phosphate slag has a P2O5 content of ≥8% and a particle size of ≤0.075 mm. The red mud or steel slag has an Fe2O3 content of ≥15% and a particle size of ≤0.075 mm.
5. The ceramsite according to claim 1, characterized in that, The bulk density of the ceramsite is 450~750 kg / m³. 3 The cylinder compressive strength is ≥0.8 MPa, the water absorption rate is 10~16%, and the yield is ≥90%; the heavy metal Pb leaching concentration is <0.5 mg / L.
6. A method for preparing ceramsite from high-lead fly ash compounded with industrial solid waste as described in any one of claims 1-5, characterized in that, Includes the following steps: S1. Weigh out the following ingredients according to the proportions: fine fly ash after water washing, municipal sludge, high-calcium fly ash or coal gangue, bentonite or clay, phosphogypsum or phosphorus slag, red mud or steel slag, and mix them evenly to obtain matrix powder. S2. The washed coarse fly ash is added to the matrix powder as aggregate, and the "core-shell" granulation process is adopted. The washed coarse fly ash particles are used as the core, and the matrix powder is evenly coated on its surface. Water is added to moisten and form spherical raw material. S3. The raw material pellets are dried, preheated, sintered, and cooled to obtain lightweight ceramsite.
7. The method according to claim 6, characterized in that, The mixing in step S1 is performed using a twin-shaft mixer for 10–15 min; The spherical raw material described in step S2 has a moisture content of 12% to 15% and a particle size of 6 to 12 mm.
8. The preparation method according to claim 6, characterized in that, In step S3, the drying temperature is 100–300°C, and the holding time is 20–30 min; the preheating temperature is 300–600°C, and the holding time is 15–20 min; the sintering temperature is 1120–1180°C, and the holding time is 20–30 min under an oxidizing atmosphere; the cooling is achieved by air cooling and rapid cooling.
9. The preparation method according to claim 8, characterized in that, The excess air coefficient of the oxidizing atmosphere is >1.
5.
10. The application of the expanded clay as described in any one of claims 1 to 5 in the preparation of landscaping substrates, lightweight fillers, or water treatment ecological filter media.
Citation Information
Patent Citations
Preparation method of fly ash ceramsite with low sintering temperature
CN113387715A
200-grade sludge fly ash ceramsite composition based on solid waste and manufacturing method thereof
CN120864865A